Fast Geometric T2-Fuzzy Based Improved Lower Extremities Stimulation Response - Hendi Wicaksono (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2010)
This study emphasizes the use of type-2 fuzzy (T2-Fuzzy) to improve the adaptive proportional-integrative-derivative (PID) control in the lower extremities. Several problems were identified from previous studies and those were the slow achievement of the target angle and the presence of oscillation in the achievement of the target blade. The oscillation occurred as the consequence of deploying the early adaptive PID which was not sufficient to overcome the lower extremities nonlinearity. The difference between proposed method of T2-Fuzzy and the others lies in the defuzzification. This research adopts a fast geometric defuzzification that maintains the level of uncertainty T2-Fuzzy in real-time. A functional electrical stimulation (FES) stimulator is proposed to design and to be connected to the computer for processing the T2-Fuzzy. This stimulator stimulates lower extremities of normal subjects each cycle, and the computer record the point of measured achievement of using a goniometer sensors mounted on a knee joint. The results show that the target point of lower extremities is achieved within three initial cycles without oscillations in the achievement of the angle. It is also found that T2-Fuzzy is able to immediately restore the point of achievement when the external parameters of control occur.